A Pilot Study - Comparison between a Novel Combination of Bioactive Glass with Clodronate and Bioactive Glass Alone as a Treatment for Chronic Periodontitis - Rosenqvist K; Gürsoy M; Könönen E; Gürsoy UK; Juppo AM (OMICS International, 2022)
Bioactive glass (BAG) and clodronate are both used for bone regeneration. In this pilot clinical study, we compared the effect of BAG and a novel BAG+clodronate combination as a topical maintenance phase treatment for chronic periodontitis. Two dental residual pockets were treated in each subject (n=10): one with BAG alone and the other with combination product, by applying the products subgingivally for 10 min once a week for four weeks. We describe the effects of these investigational products to the clinical parameters of periodontitis and two bone metabolism markers (osteoprotegerin and osteocalcin). Additionally, subjective satisfaction for the treatment was evaluated. The results must be considered as directional, understanding that further investigation is needed to confirm the findings. Based on clinical parameters measured both treatments could benefit as maintenance therapy for chronic periodontitis. The positive effect of the combination product on tooth sensitivity may bring additional benefits in comparison to the use of BAG alone. Both treatments were well tolerated and safe.